Analisis Makna “Iiwake Suru” Dan “Benkai Suru” Dalam Website Surat Kabar Bahasa Jepang Asahi.Com - Felicia Felicia (Lingua Cultura, 2011)
Verbs, particles, adjectives and conjunctions need to be understood well in learning Japanese. From a variety of verbs that exist, the author conducted an analysis of semantic field of the verbs "iiwake suru" and "benkai suru" which have the same meaning yet different usage. A literature review is applied in this study by taking data from a Japanese newspaper website asahi.com. The purpose of this study is to determine the function of the verb "suru iiwake" and "benkai suru" and to indentify when to use the verb "suru iiwake" and when to use the verb "suru benkai". After conducting ananalysis of three articles containing verb "suru iiwake" and three articles containing verb "suru benkai", the authors conclude that "iiwake suru" means both ‘argue’ and ‘do self-defense’. Besides, "iiwake suru" can be used in various types of articles. Meanwhile, "benkai suru" means both ‘do selfprotect’ and 'do self-defense'. In addition, "benkai suru" is used generally in law field especially those of related to court decision. "iwake" and "benkai" also have a similarity that is generally used with negative form.